PERAN BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM PENERIMAAN ZAKAT DI KABUPATEN KUANTAN SINGINGI TAHUN 2015 - 2017 - Iqbal, M.; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted based on establishment of National Council of Zakat in Kuantan Singingi by the regent of Kuantan Singingi and the ministry of religion based on the constitution number 38 year 1999 about the zakat management. The national council of zakat (BAZNAS) established since 2001. But in running the role still not able to reach the goals since it was built in Kuantan singing regency. It can be seen from the role of national council of zakat (BAZNAS) in Kuantan Singingi still not reach the society optimally. The purpose of this research is to describe the zakat acceptance and the factor of the inhibitor of the acceptance in Kuantan singing regency 2015-2017. This research used  qualitative approach, and was conducted in Kuantan singing regency at the office of national council of zakat Kuantan singing exactly. To collect the data in this research the researcher used interview and documentary method. The result of this research show that the national council of zakat (BAZNAS) in kuantan singing regency had been able to accept the zakat as 8 billion, but in  this case the role of the council still not optimal because the funds of zakat just from the salary of civil servant who work around Kuantan singing regency. The power of national zakat council in Kuantan singing regency is still denied, it can be seen that there is still no government rules about the zakat management. The inhibitor factor of national council of zakat (BAZNAS) in Kuantan singing regency is the quality of human resources who manage zakat and still not optimally improved. Keyword: the role of national zakat council (BAZNAS), optimization.